Study of effect of diabetes mellitus on classical risk factors for coronary artery disease - Garhwal, Suchitra; Poonia, Anil Kumar; Agarwal, Veeha (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes mellitus (DM) is increasingly prevalent in general population and is associated with increased risk for coronary artery disease (CAD). DM both directly and indirectly increases risk of CAD. Quantum of DM associated increase in classical risk factor for CAD is not exactly described. In present study, association of traditional risk for CAD and DM was analyzed. Methods: Total 150 patients with CAD were enrolled and divided into two group: group 1 with DM (84 patients) and group 2 without DM (66 patients). These two were compared and analyzed for classical risk factors for DM. Results: CAD with DM group had higher prevalence for traditional risk for CAD than CAD alone group: for Hypertension relative prevalence was 67.8 and 36.3% respectively (p<0.05); for Obesity it was 79.7 and 40.9% respectively (p<0.05) and for Dyslipidemia relative prevalence was 75 and 37.8% respectively (p<0.05). Conclusions: DM is major risk for CAD and it is also associated with increased prevalence for hypertension, obesity and dyslipidemia in affected population.